2023
DOI: 10.1021/acs.macromol.3c01632
|View full text |Cite
|
Sign up to set email alerts
|

Reversibly Interlocking of Immiscible Covalent Adaptive Networks in Solid State: A Paradigm for Enhancing Interfacial Interaction of Multicomponent Polymer Systems

Yang You,
Zheng Yue Wang,
Min Zhi Rong
et al.

Abstract: The authors of this work propose the construction of reversibly interlocked macromolecular networks (RILNs) at the interface between immiscible polymers to address the common challenge arising from compounding different polymers together. The proof-of-concept model system is made by stacking crosslinked polyether and styrene−butadiene block copolymer, which, respectively, contain reversible Schiff base and Diels−Alder (DA) bonds. By taking advantage of the synergy between the topological rearrangement of the d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 42 publications
0
1
0
Order By: Relevance
“…These methods are usually accompanied by the rupture of rubber chains, environmental pollution, and complex processes. Recently, studies into dynamic networks have suggested that reversible networks enabling interface fusion among cross-linked polymers could be a promising strategy for enhancing interactions. However, applying these dynamic network strategies to WR recycling is also challenging because irreversible vulcanization networks still dominate the rubber industry, making it difficult to replace vulcanization networks with dynamic networks . Therefore, it is necessary to develop alternative strategies to improve interactions among WR for recycling.…”
Section: Introductionmentioning
confidence: 99%
“…These methods are usually accompanied by the rupture of rubber chains, environmental pollution, and complex processes. Recently, studies into dynamic networks have suggested that reversible networks enabling interface fusion among cross-linked polymers could be a promising strategy for enhancing interactions. However, applying these dynamic network strategies to WR recycling is also challenging because irreversible vulcanization networks still dominate the rubber industry, making it difficult to replace vulcanization networks with dynamic networks . Therefore, it is necessary to develop alternative strategies to improve interactions among WR for recycling.…”
Section: Introductionmentioning
confidence: 99%